Penerapan Quadcopter sebagai Sarana Promosi Area Wisata Dengan Visualiasi Interaktif Pada Footflag - Ramadhan, Gilang; Latief, Djaenuddin; Ferdiana, Dimy; Bobby, Boy; Rofiq, Ardiyan (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Bacground: Promotion tour area is the activities promoted a tour area to prospective customers / tourists. Means for the promotion of the tourist area with take photo from common camera less attractive from aesthetics aspect.Promotion tour area must make very attractive in other that tourists can interest to visit it. Objectives: Integrating quadcopter with the camera as a device documentation of tourism area with interactive visualizations. Methods: collecting the information, literature and discussions with experts supported aeromodelling especially quadcopter, conducted by making design tool, the main function of the tool implementation and effectiveness of the test tool. Results: Quadcopter creation tool that is integrated with a high resolution camera to get a picture of the tourist area of the air. The workings of this system is the photography with a camera into the air using a quadcopter until it reaches a certain height and is used to take pictures of tourist areas from wider viewing angles. The results of the shooting will be displayed on the website as an attraction partners to increase the number of visitors on the footflag website and attract much the tourists to related tour object. Conclutions: ROCO Pantura (Robot Copter photographer reserve) a fly Devices used to take pictures from the air. This tool is equipped with a high resolution camera to get the maximum image Keywords: promotion, quadcopter, photography, tourism, website